The Progression of Treatment for Refractory Hypercholesterolemia: Focus on the Prospect of Gene Therapy - Li, Zhi-Fan; Wu, Na-Qiong (Frontiers in Genetics, 2022)
Refractory hypercholesterolemia (RH), including homozygous familial hypercholesterolemia (HoFH) and compound heterozygous familial hypercholesterolemia, is characterized by high levels of low-density lipoprotein cholesterol (LDL-C) despite existing cholesterol-lowering methods at maximal tolerable doses. Patients with RH have early onset and higher risk of atherosclerotic cardiovascular disease (ASCVD) under insufficient treatment. Therefore, it is urgent to seek new therapies to maintain the blood lipids in refractory hyperlipidemia at normal levels. Currently, new cholesterol-lowering strategies are on the market, not only at the protein level [i.e., bempedoic acid (inhibiting ATP-citrate lyase), alirocumab and evolocumab (monoclonal antibodies against PCSK9), evinacumab (monoclonal antibody against ANGPTL3)] but also at the transcript level [i.e., mipomersen (antisense oligonucleotide inhibiting ApoB), inclisiran (siRNA targeting PCSK9)], providing more options for RH patients to achieve their lipid-lowering targets. More RNA-based therapies targeting RH-related genes have been designed for the treatment. However, for a proportion of patients, especially those with LDLR deficiency, the available treatments are still insufficient. More recently, emerging genome engineering based on CRISPR/Cas9 techniques, and advanced delivery technologies such as lentiviral vectors, adenoviral vectors, adeno-associated viral vectors, lipid nanoparticles, and exosomes are being rapidly developed and implemented as novel therapies for RH. Gene therapy targeting RH-related genes has been successfully conducted in cells, mice, and non-human primates with high efficacy in lipid lowering and good tolerability. Especially the new generation of genome editing technique, base editing, performed in vivo with ideal lipid-lowering effect and limited occurrence of unwanted results. Excitingly, a phase I/II clinical study of LDLR gene replacement has been recently completed in RH patients, likely to be employed in clinical practice in the future. Furthermore, new targets for cholesterol reduction such as REV-ERB, G protein-coupled receptor, Ubiquitin specific peptidase 20 are continually being developed. This narrative review updates recent advances in treatment for RH, summarizes related clinical trials and preclinical studies, especially on the prospect of gene therapy.